KOMPETENSI GURU DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Abdullah, Abdullah (LPPM IAIN Parepare, 2018)
This study aims to find out 1) an overview of teacher competency in ICT-based PAI learning in SMP Negeri 3 Parepare, 2) form of teacher competency implementation in ICT-based PAI learning in SMP Negeri 3 Pareparel, 3) supporting and inhibiting factors for implementing teacher competence in PAI learning ICT-based in SMP Negeri 3 Parepare. This type of research is descriptive qualitative research. Research instruments are guidelines for observation, interviews, and documentation. Data collection techniques through observation, interviews, and documentation. The results of this study indicate that: (1) PAI teachers in SMP Negeri 3 Parepare, if their competencies are analyzed starting from pedagogic competencies, personality competencies, social competencies, and professional competencies and leadership competencies can be stated that PAI teachers in SMP Negeri 3 Parepare already have good competency but still needs to be improved in order to be more optimal (2) Implementation of ICT-based PAI teacher competencies in SMP Negeri 3 Parepare, analyzed from the use of theory, development of fields of study, and the use of information and communication technology (ICT) but not maximal so it still needs to be improved. (3) Supporting factors for implementing the competence of PAI teachers in SMP Negeri 3 Parepare are curriculum, teaching staff, and a conducive atmosphere of the school environment, while the inhibiting factors are facilities and infrastructure that do not support.